KVK Udalguri shows the way.... Vermicompost production as an enterprise for farmers upliftment - Ojah, Ipsita; Borah, Debasish; Boruah, Bhaskar (Indian Farming, 2020)
Active participation of farmers likeMr Hasda in vermicompostproduction, enhanced their livelihoodstatus and encouraged fellow farmersto adopt the scientific technologieswhich is truly fruitful. He is knownfor his quality products throughoutthe district viz. farmers governmentoffices, FPOs etc. and his product hashigh demand. Many more farmers,rural youth, SHGs, should come outand work hand in hand to producemore organic inputs and boostorganic farming in Udalguri Districtof Assam.